Analysis of Professional and Employability Skills among MBA Students in Maharashtra - Tilve, Madhav; Adamuthe, Amol C.; Pati, Reva S. (Journal of Engineering Education Transformations, 2026)
This study investigates the employability, willingness and professional skills of MBA students across particular districts of Maharashtra, focusing on how specific capabilities effect career outcomes. 163 students participated in a structured survey to collect information on their financial awareness, analytical skills, presentation abilities, digital literacy. Survey data examined using logistic regression, correlation and Chi-Square tests. Key forecasters of employability included financial and market literacy (β = 0.38, p = 0.002), willingness to relocate (β = 1.28, p = 0.008) and adoption of digital skills. A strong connotation was observed between job interest and relocation flexibility (χ² = 209.11, p < 0.001). Although most students showed high job interest (94.4%) and digital adaptableness (93.8%), important gaps were identified in analytical tool expertise (65.4% reported only basic SPSS skills), MS Office certification (50.6% lacked certification) and presentation skill (78.1% had fewer than three presentations). The results underscore the need for curriculum enhancement, with financial literacy modules, software-based analytical training, and structured communication practice. Recommendations highlight industry-integrated learning, certification programs, and competency-focused interventions to align management education with employer expectations.